RNM-01 Weight stability is associated with longer survival in amyotrophic lateral sclerosis. (31st October 2019) - Wei, Qianqian; Ou, Ruwei; Chen, Yongping; Chen, Xueping; Cao, Bei; Hou, Yanbing; Zhang, Lingyu; Shang, Huifang
Abstract : Background: Previous studies explored the associations between body weight index (BMI) at diagnosis, weight change after diagnosis and survival in amyotrophic lateral sclerosis (ALS). But significance of weight stability before diagnosis remains to be established. Objective: The aim of this study is to clarify the weight loss from baseline (6 months before diagnosis) to diagnostic and the effect on disease prognosis. Methods: Total of 911 patients were enrolled from 2014 to 2018 in West China Hospital of Sichuan University. BMI is divided into four subgroups: lean, normal, overweight, and obese. The formula for calculating the rate of weight change = (weight at baseline - weight at diagnosis)/weight at baseline * 100%. Survival analysis was performed using Kaplan-Meier curves and Cox proportional hazard models. Results: The mean age of onset was 55.4 ± 11.1 years. The percentage of overweight and obesity in ALS at baseline were significantly lower than healthy controls. The median of weight loss was 2.9%. 36.9% patients had weight loss more than 5%, and 16.5% of them lose weight more than 10%. Patients with bulbar onset, bulbar impairment, lower ALS functional rating scale-revised score had more serious weight loss. The Kaplan-Meier curve showed that, compared to other patients, patients with weight loss more than 10% had a shorter survival time (30.5 months vs. 48.8 months, log-rank p < 0.001). Cox analysis showed that the weight loss was found to be an independent predictor of survival after adjusting for other survival factors (HR= 1.165, p trend <0.001). Each additional increased class of weight loss was associated with a 16.5% (95% CI: 7.3%–26.5%) increased risk of mortality and worse survival. Discussion and conclusion: Our study suggested that the weight variation is associated with survival in ALS patients. This has strong implications for management of nutritional issues in ALS, that the patient education and therapy recommendation should be earlier and standardize to promote the nutritional support and prognosis.